An Empirical Study of Merdeka Belajar Kampus Merdeka Program's Impact on Soft Skills Development among University Students - Krida Singgih Kuncoro; Betty Kusumaningrum; Fitria Sulistyowati; Iffatul Ulya; Dhimas Nur Setyawan; Wuryan Tri Kartiko (Buana Pendidikan, 2023)
This empirical study aims to investigate the impact of the Merdeka Belajar Kampus Merdeka (MBKM) program on the development of students' soft skills in universities. The MBKM program, introduced by the Indonesian government, aims to enhance students' soft skills and prepare them for the challenges of the professional world. The study employs both quantitative and qualitative approaches to gather data from students who have participated in the MBKM program across various universities in Indonesia. The research findings reveal that the MBKM program has a significant impact on the development of students' soft skills. Out of the 83 respondents who participated in the program, 85% reported an improvement in their soft skills after participating in MBKM. Specifically, the program was found to enhance students' communication, empathy, socialization, creativity, problem-solving, and cultural respect abilities. The study highlights that students with work experience tend to have more developed soft skills.